Labor epidural analgesia versus without labor epidural analgesia for multiparous women: a retrospective case control study - Luo, Shuzhi (BMC Anesthesiol, 2021)
BACKGROUND: Labor epidural analgesia (LEA) effectively relieves the labor pain, but it is still not available consistently for multiparous women in many institutions because of their obviously shortened labor length. METHODS: A total of 811 multiprous women were retrospective enrolled and firstly divided into two groups: LEA group or non-LEA group. And then they were divided into seven subgroups and analyzed according to the use of LEA and cervical dilation. The primary outcomes (time intervals, blood loss and Apgar scores) and secondary outcomes (maternal demographic characteristics and birth weight) were collected by checking electronic medical records. RESULTS: The prevalence of using LEA in multiprous women was 54.5 %. Using LEA significantly lengthened the duration of labor stage by 56 min (P < 0.001), increased the blood loss (P < 0.001) and lowered Apgar scores (P = 0.001). In the comparison of sub-group analysis, using LEA can obviously prolong the duration of first-second stage in women with 2 cm cervical dilation (P < 0.001) and 3 cm cervical dilation (P = 0.014), while there was no significant difference with 4 cm or more cervical dilation (P = 0.69). Using LEA can significantly increased the blood loss when the initiation of LEA in the women with 2 cm cervical dilation (P < 0.001) and 3 cm cervical dilation (P = 0.035), meanwhile there were no significantly differences in the women with 4 cm or more cervical dilation (P = 0.524). Using LEA can significantly lower the Apgar scores when the initiation of LEA in the women with 2 cm cervical dilation (P = 0.001) and 4 cm or more cervical dilation (P = 0.025), while there were no significantly differences in the women with 3 cm cervical dilation (P = 0.839). CONCLUSIONS: Labor epidural analgesia for the multiparous woman may alter progress of labor, increase postpartum blood loss and lower Apgar scores. Early or late initiation of LEA should be defined as with cervical dilatation of less or more than 3 cm and the different effect should be understand. TRIAL REGISTRATION: ChiCTR2100042746. Registered 27 January 2021-Prospectively registered, http://www.chictr.org.cn.